Update 2021: Corona-Pandemie – Herausforderungen für die Geriatrie - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2021)
Nobody supposed that after one year of the pandemia, the SARS-CoV-2 Virus and its emerging mutants dominates the press, our lives and the health system as a whole. As for Geriatric Medicine, many things have also changed: The majority of COVID-19 patients are no more the (oldest) old and mortality is less observed in multimorbid persons, as most of them have been vaccinated. (Oldest) old persons are still especially vulnerable to die due to a COVD-19 infection. In longterm care, a significant higher mortality was seen in the former waves, but now, some longterm care facilities have more places that they can fill. This is a situation that many European countries would never have anticipated. Ressource allocationin stormy times is now more openly discussed, especially who should be admitted to intensive care units. This has led to more detailed and new guidelines which may help even when the pandemia is over. Here, some thoughts regarding the care of older adults in times of the pandemia are discussed.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Coronavirus pandemic; COVID-19; diet; geriatrics; Long-Covid; multimorbidity